Effect of nano-enhanced phase change material on the thermal management of a 18650 NMC battery pack. (1st August 2023) - Talele, Virendra; Zhao, Peng
Abstract: Thermal control employing phase change material (PCM) for battery cooling application is quite well recognized throughout recent years. However, due to its limitations of poor thermophysical property, it is a less favoured thermal design for high voltage battery packs. Advanced nano-enhanced PCM appears to be particularly promising in PCM aided passive thermal design since it has greater higher thermal conductivity with acceptable latent heat. In present study, the CFD numerical analysis is developed considering battery pack operating at varying ambient temperature for 4S4P configured high voltage cathodic chemistry NMC 8:1:1 lithium-ion cell with 12Ah capacity and 14.2 network voltage. The objective of current study is to numerically investigate passive thermal performance of a battery pack, in which PCM is modeled based on enthalpy-porosity phase-change computational framework. A comparative thermal performance is investigated between conventional paraffin wax PCM and nano-enhanced Al2 O3 PCM. The battery pack is considered operating at 1C and 2C constant charge rate with mimicked ambient temperature of 25 ° C and 35 ° C . Concluding results show, conventional paraffin wax PCM is incapable of providing better battery maximum temperature delay performance as compared to nano-enhanced PCM, this happens due to the poor heat transfer rate of conventional paraffin wax PCM which causes it to become liquidous state prematurely as compared to nano-enhanced PCM. Overall battery thermal effectiveness is found to be increased with nano-enhanced PCM as compared to conventional paraffin wax PCM. Highlights: Computational investigation of cathodic NMC 8:1:1 18650 battery pack thermal performance using novel nano enhanced PCM. An in depth thermal modeling strategy of nano enhanced PCM for BTMS applications is investigated. A comparative study between conventional paraffin wax PCM and novel nano enhanced PCM for battery thermal management studied. The thermal effectiveness of battery packs with paraffin wax PCM and nano enhanced PCM is empirically correlated.